Linear A texts in phonetic transcription : and commentary - University of Kansas (2000)
[Dt.:] John G. Younger hat auf dieser Website die phonetischen Transskriptionen etlicher Linear A-Texte zusammengestellt. Zusätzlich gibt es Informationen zu Sprache, Zeichen und Entzifferung von Linear A. - [Engl.:] John G. Younger has collected the phonetic transcriptions of a number of Linear A texts on his website. In addition there is information on language, characters and decipherment of Linear A.